The Efforts of the Universitas Muhammadiyah Sinjai to Produce Graduates with Entrepreneurship Spirit - Syamsuddin Syamsuddin; Abdul Gani Gaffar; Noviana Nurtasmi (Jurnal Ad'ministrare, 2021)
Universitas Muhammadiyah Sinjai (UMSi) as one of the universities that conducts Catur Dharma College in the fields of education, research, service and Al-Islam Kemuhammadiyaan which is expected to play a role in national development by improving students' skills and knowledge according to the needs and relevance of the world of work as a whole. systematically and directed by trying to develop an entrepreneurial spirit and entrepreneurship education in order to produce graduates with an entrepreneurial spirit in order to be able to reduce the educated unemployment rate in Sinjai Regency. This study uses a qualitative method approach, with data collection techniques carried out, namely; documentation; in-depth interviews and direct observation. The stages in this research are, observation; instrument preparation; data collection; data analysis and model design. The results of this study indicate that the efforts made by the Universitas Muhammadiyah Sinjai have produced graduates who have an entrepreneurial spirit, although not yet maximal, because the marketing and production processes are not yet on a large scale.